Analisis Tingkat Efisiensi Kinerja Lembaga Keuangan Mikro Syariah Dengan Pendekatan Data Envelopment Analysis (DEA) - Umi Rachmah Damayanti (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2018)
Microfinance institutions is one of the pillars in the financial intermediation process. The potential and opportunities that so great on the SMEC has been attracting the business of microfinance with wonderful, even the realm of social empowerment microfinance lately has been transformed into the microfinance business with commercial. Map of the competition strict automatic this will bring consequences of the microfinance business changed. Given the role of Islamic microfinance institutions (LKMS) is enormous in encouraging the development of micro enterprises, then the existence of LKMS need to remain guarded and enhanced performance. This research aims to know how does the level of efficiency of LKMS performance and efficiency improvement measures LKMS. The method of DEA (Data Envelopment Analysis) used to measure efficiency and identify measures to increase the efficiency of LKMS. The results of the research there is a finding that LKMS have a value score efficiency below 1, meaning the institutions in conducting his business inefficient. The cause of the occurrence of LKMS [there is the magnitude of the burden of input that are not offset with the output generated.